Unlocking The Puzzle: Locus of Control, Fintech and Financial Literacy in Shaping Financial Behavior - Kiswanti, Hanny Mahasih; Khouroh, Umu; Yuniarti, Sari; Begum, Farhana; Herdiyanti, Indyah (SRIWIJAYA INTERNATIONAL JOURNAL OF DYNAMIC ECONOMICS AND BUSINESS, 2023)
This study is intended to analyze the financial management behavior of merchants in Pasar Besar, Malang City interms of locus of control and fintech perspectives by presenting financial literacy as a mediation variable. The research design used is quantitative with explanatory research methods. The study population is merchants in Pasar Besar, Malang City with probability sampling techniques using the simple random sampling method. Data analysis techniques using partial least square-structural equation model (PLS-SEM). The results showed that locus of control and fintech have a significant positive effect on financial management behavior; Locus of control and fintech have a significant positive effect on financial literacy. The results also stated that financial literacy can mediate the influence of locus of control and fintech on financial management behavior.